Combined effect of underwater ultrasound and custom-made insoles in rheumatoid arthritis: a randomized controlled trial - Ozcelep, Omer Faruk; Demir, Ceren; Okumus, Elife Ceyda; Canli, Mehmet; Alkan, Halil (Springer London Ltd, 2026)
Background To investigate the effects of underwater ultrasound therapy alone and in combination with custom-made insoles in individuals with rheumatoid arthritis (RA). Methods This single-blind, randomized controlled trial included 75 patients with mild-to-moderate RA and foot pain, who were randomly allocated into three groups: control group (CG), underwater ultrasound group (UG), and underwater ultrasound plus custom-made foot insole group (IG). Interventions were applied over a 6-week period. Outcome measures included the Health Assessment Questionnaire (HAQ), Manchester-Oxford Foot Questionnaire (MOFQ), Timed Up and Go test (TUG), Berg Balance Scale (BBS), Static Plantar Pressure Distribution (SPPD), Single Heel-Rise Test (SHRT), and ankle circumference (AC). Assessments were performed before and after the intervention period. Results Significant time effects were observed for most outcome measures, indicating overall improvements after the intervention period across all groups (p < 0.05), except for AC. A significant group & times; time interaction was found for HAQ (p = 0.002, eta 2 = 0.209) and selected SPPD parameters (RF, RB, and LB; p < 0.05), suggesting differential changes over time between groups. No significant group & times; time interactions were observed for MOFQ, TUG, BBS, SHRT, or AC, indicating comparable clinical improvements among groups. In contrast, SPPD demonstrated significant between-group differences, particularly in the group receiving custom-made foot insoles (p < 0.05). Conclusion Underwater ultrasound therapy was associated with overall improvements in functional status, mobility, balance, and muscle performance in patients with rheumatoid arthritis. While clinical outcomes improved similarly across groups, the addition of custom-made insole mainly enhanced plantar pressure distribution, indicating a primary biomechanical benefit.
Keywords: Custom-Made Insole; Plantar Pressure; Rheumatoid Arthritis; Ultrasound